1993
DOI: 10.1159/000243923
|View full text |Cite
|
Sign up to set email alerts
|

Sighs and Their Relationship to Apnea in the Newborn Infant

Abstract: To test the hypothesis that sighs are mechanistically important in triggering apnea, we studied 10 preterm infants, group 1: body weight 1.8 ± 0.1 kg, gestational age 33 ± 1 weeks, postnatal age 21 ± 4 days, and 10 term infants, group 2: body weight 3.9 ± 0.15 kg, gestational age 40 ± 0.4 weeks, postnatal age 1.4 ± 0.2 days. Instantaneous ventilatory changes associated with a sigh were studied in another 10 preterm infants, group 3: body weight 1.6 ± 0.11 kg, gestational age 32 ± 0.4 weeks, postnatal age 25 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 10 publications
2
19
0
1
Order By: Relevance
“…As already reported [3], sighs are more frequent in REM sleep than in NREM sleep. Preterm infants show a higher rate of sighs than term infants (group I -preterm: 0.51 sighs/min; group III -term: 0.36 sighs/min), confirming the findings of Alvarez et al [4]. The frequency of sighs decreases with increasing gestational age.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As already reported [3], sighs are more frequent in REM sleep than in NREM sleep. Preterm infants show a higher rate of sighs than term infants (group I -preterm: 0.51 sighs/min; group III -term: 0.36 sighs/min), confirming the findings of Alvarez et al [4]. The frequency of sighs decreases with increasing gestational age.…”
Section: Discussionsupporting
confidence: 87%
“…Generally, the total number of central apneas 15 s and the total number of sighs decrease with increasing gestational age. Alvarez et al [4] reported that of the sigh-associated apneas he found in his study, 48% preceded a sigh. In our investigations, we did not try to prove the existence of apneas preceding any kind of sigh because we interpret postapnea sighs as an inspiratory overreaction to the preceding central apnea or respiratory pause.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Infants sigh frequently during sleep (Alvarez et al 1993) so adoption of this guideline renders a relatively large proportion of MBW testing cycles unreportable. There are currently few data to formally evaluate the recommendation to exclude testing cycles containing sighs.…”
Section: Introductionmentioning
confidence: 99%